PENGARUH KEJELASAN SASARAN ANGGARAN, KESULITAN SASARAN ANGGARAN, PENGENDALIAN AKUNTANSI DAN SISTEM PELAPORAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (Studi Pada Satuan Kinerja Perangkat Daerah Kabupaten Pelalawan) - Yulianti, Reni; ', Hardi; ', Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to determine the effect of budget goal clarity, budget goal difficulty, accounting control and reporting system to the accountability of local government institution in Pelalawan. This study used a survey method of work units in Pelalawan. The sample was 128 respondents. The population in this study was 32 offices in Pelalawan District on education. Type of the data was primary data with the method of data collection by using questionnaires. The method of data analysis in this study was multiple regression (multiple regression) by using software SPSS version 17.0. Based on the results of simultaneous test showed that budget goal clarity, budget goal difficulty, accounting control and reporting system gave significantly affect to the accountability of government institution. The degree of influence of each independent variable on the dependent variable can be determined by doing partial test (t-test). The results showed that variable budget goal clarity, budget goal difficulty, accounting control and reporting system had a significant effect on performance accountability of government institution.Key words: budget goal clarity, budget goal difficulty, accounting control, reporting system and performance accountability of government institution